Learning to Teach: Ethnomethodological Analysis of Pre-Service Teachers' Instructional Decisions - Raziye Sancar; Deniz Deryakulu (Anı Publishing, 2020)
In the research, it was aimed to determine how pre-service teachers establish the meaning regarding instructional decision making based on their first instructional experiences. The research was designed as ethnomethodological research by adopting a qualitative research approach. The study group of the research consists of 16 (9 female, 7 male) pre-service teachers who have never had any teaching experience before. The data sources were interviews and video recordings obtained from pre-service teachers' in-classroom teaching experiences. The meaning of pre-service teachers regarding instructional decision making; having (the personal characteristics, content knowledge, and teaching skills), doing (the close relationship and communication with the student, the teaching method, classroom management, and assessment method), and aiming of (reach-in student life and social life). Pre-service teachers' meaning-making about being a teacher should be combined with their teaching and learning process for successful teacher education.